Design of a Speed Sensorless Control System on a DC Motor using a PID Controller - Harini, Bernadeta Wuri; Gunadi, Theodore Galeno; Mahardika, Shakuntala Gema; Pangestu, Sirilus Praditya; Putri, Regina Chelinia Erianda; Mardikus, Stefan (International Journal of Applied Sciences and Smart Technologies, 2025)
The speed sensorless control system on a DC motor is a DC motor speed control system that does not use a speed sensor to measure the motor speed. The motor speed value is estimated by an observer from the stator current and voltage that are measured using a sensor. This study uses an R observer method.  The difference between the estimated speed and the reference speed is then used by the PID controller to adjust the motor speed to match the desired reference speed. PID parameter tuning using heuristic method. With a setpoint of 6800 RPM and using a combination of Kp = 0.5, Ki = 0.05, and Kd = 0.34, a speed value of 6792.76 RPM was obtained. Sensorless motor speed control using a PID controller produces an optimal system with a low Steady State Error (SSE) value of around 0.1%, very small oscillations of 0.39%, a fast rise time of 4 seconds, and a fast settling time of 6 seconds.